PERAN KEARIFAN LOKAL DESA ADAT PENGLIPURAN DALAM KETAHANAN PANGAN RUMAH TANGGA PASCA PANDEMI COVID-19 SEBAGAI DESA WISATA BERBASIS MASYARAKAT - Siti Widiati; Mirajiani Mirajiani; Asih Mulyaningsih (JURNAL AGRIBISNIS TERPADU, 2023)
Penglipuran Tourism Village is one of the Traditional Villages developed in Indonesia which is located in Bali, in its management the Traditional Village is very concerned about the environment and local wisdom, as well as the concept of community-based development. The majority of people's goods are artisans and related to tourism, this has led to a reduction in working hours during Covid-19, so this has also had a negative impact on family income. During the post-Covid-19 pandemic, the Penglipuran indigenous village community was visited by tourists again and the economic system was better than during the Covid-19 pandemic, but the economic system was not as stable as before the pandemic, this was shown by the level of household food security, where people still there are those who carry out Food Coping Strategy at Level I as much as 80% and Level II as much as 20%, the Coping Strategy Level, and do not carry out drastic steps or food fulfillment mechanisms or Coping Strategy at Level III, Penglipuran Village Indigenous people as a Food Security Tourism Village based on the mechanism of fulfilling food needs or Food Coping Strategy at the household level.